ETHANOL PRODUCTION FROM FERMENTATION OF ARUM MANIS MANGO SEEDS (MANGIFERA INDICA L.) USING Saccharomyces Crevisiaea - Masturi, Masturi; cristina, amelia; Istiana, Nurul; Sunarno, Sunarno; Dwijananti, Pratiwi (Jurnal Bahan Alam Terbarukan, 2017)
The increase of energy needs coupled with the decline in fossil fuel production, requires other sources of energy to meet those needs. One of the solution is using renewable energy. Bioethanol is one of the alternatives to the fossil fuel. This study was aimed at determining the exact mass of mango seeds in producing high grade bioethanol. Bioethanol was produced by fermentation of arum manis mango fruit seed using bakers yeast, Sacczharomyces cerevisiae.  The arum manis mango seeds were known to contain carbohydrate contents of 19.53%. The study was conducted by using different mass of mango seeds 25, 35 and 45 g resectively. The study showed that the samples of 25, 35 and 45 g produce ethanol with concentration of 4.78, 6.64 and 1.48%. These results indicated that the mass of 35 g mango seeds produced highest ethanol content.